Effect of Vitamins and Amino Acids as Cryoprotectant Solution Supplementation for the Cryopreservation of Tambaqui Semen (Colossoma macropomum) - Lopes, Júlia Trugilio; Oliveira-Araújo, Mayara Setúbal; do Nascimento, Renata Vieira; Ferreira, Yasmin Maia; Montenegro, Assis Rubens; Salmito-Vanderley, Carminda Sandra Brito (Acta Scientiae Veterinariae, 2018)
Background: The addition of antioxidant substances to a cryoprotective solution can increase its protective capacity, shielding spermatozoa from the oxidative stress caused by the seminal cryopreservation process. However, there is no record of a seminal cryopreservation protocol of tambaqui (Colossoma macropomum) using antioxidants as a supplement to the cryoprotective solution. Thus, the objective of this study was to evaluate the effects of adding vitamin C, vitamin E, cysteine, and/or taurine to the seminal cryopreservation of tambaqui. Materials, Methods & Results: Pools of semen (n = 10) were diluted in cryoprotective solutions supplemented with: vitamin C (T1), vitamin E (T2), vitamin C + vitamin E (T3), cysteine (T4), taurine (T5), and taurine + cysteine (T6). The control treatment (T7) was not supplemented. Diluted semen was loaded in 0.5 mL straws, frozen in a dry-shipper, stored in a cryogenic cylinder, and then thawed in a water bath (45ºC for eight seconds). The quality of fresh and cryopreserved semen was evaluated by measuring total motility, progressive motility, curvilinear velocity (VCL), straight line velocity (VSL), average path velocity (VAP), linearity, and straightness using a computerized system of sperm analysis. Sperm membrane integrity parameters were analyzed using eosin-nigrosin staining, sperm morphology was assessed using pink bengal staining, and motility duration was measured by a digital timer. Data were analyzed using the statistical program SAS (2002) and the results were expressed as means ± standard error of the mean. The results showed that, in general, there was no significant increase in seminal quality when antioxidants were added to the cryoprotective solution. The T5 treatment promoted an increase (P < 0.05) in progressive motility when compared to T1 (6.33 ± 1.14% and 2.98 ± 0.88%, respectively). However, it did not differ significantly (P > 0.05) from the other treatments. Treatments T2 and T5 presented the highest values of VCL (34.74 ± 2.58 and 33.60 ± 1.81 μm.s-1, respectively). These were higher (P < 0.05) than T1 (26.31 ± 1.64 μm.s-1) but not different (P > 0.05) from the T7 control (30.87 ± 1.49 μm.s-1). The VSL and VAP results showed that T1 presented the lowest velocity (9.89 ± 1.75 and 15.06 ± 1.92 μm.s-1, respectively) compared to the other treatments (P < 0.05) that did not differ from each other. Combining the two vitamins (T3) or the two amino acids (T6) was not advantageous in relation to the use of only one of these antioxidants. Discussion: The present study reports, for the first time, results of the addition of antioxidants to the tambaqui seminal freezing medium. The addition of taurine and vitamin E, although not significantly different from the control treatment, resulted in a tendency to increase sperm kinetics. This effect may be due to the action of taurine as a regulator of Ca2+ transporters, which is necessary to trigger sperm activation, and to the ability of vitamin E to scavenge reactive oxygen species produced during lipid peroxidation. On the other hand, the reduced sperm quality observed when vitamin C was used may have been related to the toxicity caused by a high concentration of this vitamin. In addition, once the safe dose of antioxidants has been exceeded, the normal physiological functions of reactive oxygen species can be inhibited. Thus, it is concluded that the use of vitamin E and taurine promotes promising results of curvilinear velocity after thawing of sperm. Therefore, these treatments are recommended, as well as more tests to determine their optimal concentrations.